Apraclonidine—An eye opener - Fierz, Fabienne C.; Disse, Leah R.; Bockisch, Christopher J.; Weber, Konrad P. (Frontiers in Ophthalmology, 2022)
Pharmacological testing with apraclonidine eye drops induces a typical reversal of anisocoria in patients with Horner’s syndrome. Moreover, apraclonidine was observed to have an elevating effect on the upper eyelid in Horner’s syndrome as well as in healthy subjects, which is thought to be mediated by alpha-1 adrenergic receptors present in the Muller’s muscle. We aim to quantitatively investigate the effect of apraclonidine on eyelid position in patients with Horner’s syndrome compared to physiological anisocoria based on infrared video recordings from pupillometry. We included 40 patients for analysis who underwent binocular pupillometry before and after apraclonidine 1% testing for evaluation of anisocoria. Vertical eyelid measurements were taken from infrared videos and averaged from multiple pupillometry cycles. Receiver operating characteristics (ROC) curves were calculated to determine the optimal cut-off value for change in eyelid aperture pre- and post-apraclonidine. A decrease of inter-eye difference in aperture of >0.42mm was discriminative of Horner’s syndrome compared to physiological anisocoria with a sensitivity of 80% and a specificity of 75%. Our data confirm an eyelid elevating effect of the apraclonidine test, more pronounced in eyes with a sympathetic denervation deficit. Measuring the eyelid aperture on pupillometry recordings may improve the diagnostic accuracy of apraclonidine testing in Horner’s syndrome.